1992
DOI: 10.1021/jm00084a005
|View full text |Cite
|
Sign up to set email alerts
|

CoMFA analysis of the interactions of antipicornavirus compounds in the binding pocket of human rhinovirus-14

Abstract: A CoMFA analysis of eight compounds related to disoxaril whose X-ray structures bound to HRV-14 had been determined resulted in a strong positive correlation of activity with steric effects of the compounds, particularly toward the pore end of the compound binding site, and no correlation with electrostatic effects. These results confirm what had been previously found, that the activity of these compounds was highly dependent upon their hydrophobic nature as expressed by log p. The CoMFA study also confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 1 publication
(2 reference statements)
0
18
0
Order By: Relevance
“…Although bulk is important, the nature of the binding pocket imposes limits on the amount of bulk and how it is oriented. Even though modelling showed that 10 could be accommodated within the binding pocket, it has been proposed that for Disoxaril and its analogues excessive bulk in the phenyl region of the inhibitor leads to decreased activity (Diana et al, 1992). Our modelling experiments indicated that the dibenzyl group is located in what would be the phenyl region of Disoxaril.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although bulk is important, the nature of the binding pocket imposes limits on the amount of bulk and how it is oriented. Even though modelling showed that 10 could be accommodated within the binding pocket, it has been proposed that for Disoxaril and its analogues excessive bulk in the phenyl region of the inhibitor leads to decreased activity (Diana et al, 1992). Our modelling experiments indicated that the dibenzyl group is located in what would be the phenyl region of Disoxaril.…”
Section: Discussionmentioning
confidence: 73%
“…The steric factors discussed above could also apply in this case. In addition, it was reported that in some Disoxaril analogues the phenyl ring appeared to be in a stacking configuration with Tyr 12 8 and Tyr 1S2 of the capsid protein (Diana et al, 1992). Such pitype interactions may contribute to activity, and in the case of 18 such an interaction is obviously not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, inhibitors behave differently in the binding process. Most prefer an orientation with the isoxazole at the so-called heel of the pocket, whereas other analogues choose the opposite direction [3,6,7]. Crystal structures of WIN compounds and several other co-crystallised inhibitors from the Brookhaven Protein Databank (PDB) [8] served as sources for pharmacophore model generation, docking processes, and virtual library design in this study.…”
Section: Introductionmentioning
confidence: 99%
“…A number of applications of CoMFA in medicinal chemistry have been reported [18][19][20][21][22][23][24][25][26][27][28][29][30]. However, the methodology in its present state offers no explicit provision for management of different conformations of molecules with rotatable bonds [28].…”
Section: Introductionmentioning
confidence: 99%